Institutionalising parliament in South Africa: the challenges to parliamentary leadership - Hennie Kotzé (Acta Academica, 2001)
As democratisation moves from a transitional phase to one of consolidation, the legislature becomes integral to the process. In South Africa, the conflict-regulating capacity of the new democratic system is determined to a large extent by the constitutionally created institutions, on the one hand, and political leadership, on the other. This study will attempt to gauge the attitudes of the South African elites and the public to the performance or worth of parliament as an emerging institution in the aftermath of the country’s first democratic elections, and in so doing, to ascertain the progress of the institutionalisation process. It is argued that attitudes are based primarily upon the performance of parliament, with the parliamentary leadership and the opportunities and dilemmas it faces forming the core of this discussion.